Algorithm of prognosis of psychological adaptation-maladaptationas the basis of personalized psycho-correction of patients with dermatological diseases with different levels of vital threat - Abdryakhimova, T.; Skrebtsova, G. (Journal of Education, Health and Sport, 2023)
Purpose: to substantiate the algorithm for predicting the state of psychological adaptation - maladaptation of patients with dermatological pathology with different levels of vital threat, on the basis of which to develop personalized psychocorrection programs for this contingent, and to evaluate the effectiveness of their implementation. . Contingent and research methods. Based on the principles of biomedical ethics and deontology, we comprehensively examined 120 dermatological patients who were treated in three branches of the clinic "Dr. Zapolska Clinic" during 2020-2022, namely: 60 patients with non-vital dermatological diseases (seborrheic keratosis L82, condylomas A63.0, angiomas D18.0, pigmentation disorders L80), and 60 patients with dermatological diseases posing a vital threat ( melanoma C43, basal cell carcinoma C44, skin carcinoma in situ D04). Results. Among patients with dermatological diseases, there are both psychologically adapted and maladapted individuals, regardless of the vitality/non-vitality of the pathological process. The process of formation of psychological maladaptation in patients with dermatological diseases with different levels of vital threat does not have nosospecificity, but depends on the initial state of the adaptive resource base of the individual, first of all, its psychosocial and individual-psychological components. Summarizing the obtained results made it possible to identify three main blocks of characteristics that cover a wide range of biological, individual-psychological, social-environmental and psychosocial factors, which we defined as factors/markers of psychological adaptation-maladaptation in patients with dermatological diseases with different levels of vital threat: psychoemotional , psychosocial and personal. Based on the analysis of determined markers of psychological adaptation-maladaptation using mathematical methods, an algorithm for assessing and predicting psychological maladaptation in this contingent of patients is proposed. This algorithm determines the criteria of personification, the structure and scope of developed psychocorrective measures at different degrees of risk of psychological maladaptation in patients with dermatological diseases with different levels of vital threat. A three-stage system of psychocorrective interventions (assessment-diagnostic, clinical-therapeutic, and correction-adaptation stages) has been developed, united by the complexity and continuity of correction, psychotherapeutic, and adaptation measures. At the assessment-diagnostic stage, the prognosis of the development and progression of maladaptation is assessed, which ensures the personification of psychocorrective interventions, which are carried out mainly at the clinical-therapeutic stage, the positive effect of which is fixed at the last, corrective-adaptation stage. The evaluation of the effectiveness of these measures proved their effectiveness in eliminating psychopathological manifestations (depression and anxiety), improving the quality of life and social functioning, and increasing vitality and resilience. Conclusion. Personalized psychocorrection of patients of dermatological practice with different levels of psychological maladaptation may be recommended for the introduction into health care practice.